2007 IEEE International Electron Devices Meeting 2007
DOI: 10.1109/iedm.2007.4418886
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Implementation of Dopant-Segregated Band-edge Metallic S/D junctions in Thin-Body SOI p-MOSFETs

Abstract: band-edge silicide, such as PtSi, provides an additional leverage to further reduces the contact resistivity by This paper proposes the implementation of a dopant promoting thermionic injection. Depending on the process segregated band-edge silicide using implantation-to-silicide sequence, dopant-segregation (DS) technique can be and low temperature activation (500°C). The integration of implemented in three different flavours [5]: i) implantation platinum silicide coupled to boron segregation demonstrates a i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…The efficiency of dopant-segregated Schottky contacts has been demonstrated. 9,10 It has been shown that a sub-100 meV barrier can be obtained consistently with the boron pile-up observed at the PtSi/Si interface. A new stateof-the-art current drive performance has been established for Schottky barrier MOSFETs at L G = 25 nm: 7 0N = 530 μΑ/μπι at K G = F D = -1.1 V. Figure 4 demonstrates that metallic S/D is competitive with the best unstrained SOI pMOS technologies.…”
Section: More Moorementioning
confidence: 60%
See 1 more Smart Citation
“…The efficiency of dopant-segregated Schottky contacts has been demonstrated. 9,10 It has been shown that a sub-100 meV barrier can be obtained consistently with the boron pile-up observed at the PtSi/Si interface. A new stateof-the-art current drive performance has been established for Schottky barrier MOSFETs at L G = 25 nm: 7 0N = 530 μΑ/μπι at K G = F D = -1.1 V. Figure 4 demonstrates that metallic S/D is competitive with the best unstrained SOI pMOS technologies.…”
Section: More Moorementioning
confidence: 60%
“…/ 0 N VS. / 0 FF in state-of-the art of S/D pMOS on SOI indicating that boron dopant-segregated devices lead both Schottky barrier and conventional unstrained thin-film SOI technologies 9. …”
mentioning
confidence: 99%
“…A new state-of-the-art current drive performance has been established for SB-MOSFETs at 25 nm of gate length: Figure 14 also demonstrates that metallic S/D competes with best unstrained channel SOI p-FET technologies. A record RF performance for a 30 nm p-type unstrained thin-film fully depleted SOI SB MOSFET has been demonstrated with a f T of 180 GHz [16]. The effect of strained semiconductor is also thoroughly studied: carrier injection from a metallic junction should benefit from band splitting and from the corresponding Schottky barrier height reduction.…”
Section: Metallic Schottky Source/drain Mosfetsmentioning
confidence: 99%
“…The expected benefit is to considerably reduce the specific contact resistance of the metal/semiconductor junction while keeping activated dopants sharply localized at the interface. In the framework of the European projects, the efficiency of dopant segregated Schottky contacts has been demonstrated [16][17][18]. The implementation of dopant segregated contact is illustrated by considering the following three distinctive features: (i) implant-to-silicide (ITS), (ii) band-edge low Schottky barrier (SB) to holes (PtSi) and (iii) thermal budget limited to 500…”
Section: Metallic Schottky Source/drain Mosfetsmentioning
confidence: 99%
“…11,12 Recently, short-channel p-type SB-FETs with NiSi and PtSi contacts and boron dopant segregation have been demonstrated that show oncurrents comparable to conventional unstrained SOI FETs. 13,14 Traditionally, an Ohmic contact between a semiconductor and a metal is formed by highly doping the semiconductor. 15 However, for a fully depleted SOI MOSFET channel doping causes merely a shift of the threshold voltage and reduced carrier mobility.…”
Section: Introductionmentioning
confidence: 99%